Application of Square and Oblong Pore Shapes in Rotating Membrane Emulsification to Produce Novel Particulate Products - Nita Aryanti; Richard Andrew Williams; Qinchung Yuan (Reaktor, 2020)
Rotating membrane emulsification (RMR) has been intensively developed and applied for producing emulsion as well as particulate products such as microcapsules. Polyurea microcapsules were generally prepared by interfacial polycondensation polymerisation with addition of modifier to produce more stable microcapsules. In this research, development of the RMR was applied for producing polymer particles stabilised by nanoparticle without any addition of surfactant or modifier. Two types of membrane pores, the square (Type-A) with hydraulic diameter (Dh) of 84 mm and oblong pores with an aspect ratio of 0.33 (Type-B) having Dh of 69 mm was investigated. For the membranes designed in this research, pore shape A membrane could produce good uniformity in both polyurea microcapsule and polymer particle. In the polymer stabilised particle, this membrane type obtained a narrower size distribution than the usage for o/w emulsification. Reasonable uniform particles at high membrane rotation speed could also be achieved with the use of Type-A membrane. The uniformity confirmed that there was only minor breakup of products during operation at high membrane rotation. This attractive feature was significant in the production of fragile or shear-sensitive particulate products since the delicate structure of these products is possibly easy to destroy at high membrane rotation speed.  Keywords: polyurea microcapsules; particles stabilised nanoparticles; slotted pore